Penyelesaian Soal Limit Fungsi Trigonometri dengan Solusi Cepat pada siswa SMA - Iin Ariyanti; Nafisa Nur Zaqiyah (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
The purpose of this service is to help students deal with the shortage of time when working on multiple choice math problems, especially in the trigonometric function limit material. This activity was carried out on April 24, 2019 at SMAN 1 Tamban, Barito kuala, South Kalimantan, attended by 25 students as participants. The implementation of this activity consists of opening and introduction, explanation and application of problem solving, then practice questions and gift giving, as well as closing and group photos. The material for the quick solution of trigonometric function limit problem solving consists of trigonometric limits using the spruck rules, trigonometric limits using the delete rules of